Differential Roles of GnRH-I and GnRH-II Neurons in the Control of the Primate Reproductive Axis - Urbanski, Henryk (Frontiers in Endocrinology, 2012)
In vertebrates, gonadotropin releasing-hormone (GnRH) represents the primary neuroendocrine link between the brain and the reproductive axis, and in some species up to three different forms of GnRH have been detected. Until recently, it had been assumed that humans and nonhuman primates only express one form (GnRH-I), but it is now clear they also express a second form (GnRH-II). GnRH-II, like GnRH-I, is highly effective at stimulating gonadotropin release, both in vitro and in vivo, but the neurons that produce GnRH-II are completely distinct from those producing GnRH-I. Moreover, GnRH-II and GnRH-I producing neurons respond very differently to estradiol; specifically, estradiol stimulates GnRH-II gene expression in the former and inhibit GnRH-I gene expression in the latter. Consequently, the negative feedback action of estradiol may be mediated exclusively by the subpopulation of GnRH neurons that express GnRH-I, while the positive feedback action may be mediated exclusively by the subpopulation that expresses GnRH-II. Taken together, these findings raise the possibility that two completely different GnRH neuronal systems participate in the control of primate reproductive physiology. The primary role of GnRH-I neurons is likely to be focused on the maintenance and modulation of tonic pulsatile LH release, whereas the primary role of GnRH-II neurons is likely to be focused on the generation of the preovulatory LH surge. This functional segregation of the primate neuroendocrine reproductive axis lends itself for novel targetted approaches to fertility control and for treatment of human reproductive disorders.